(untitled) (Research, Society and Development, 2021)
This article discusses the production of waste during the construction process of the Kilamba centrality and the impacts caused by their release in the urban ecosystem. To answer our research questions, a strategic strategy used was the qualitative one through the case study. The objective was to identify the socio-environmental impacts on the urban ecosystem of Luanda caused by the disposal of proven waste from the construction of the Kilamba centrality. Our understanding of the case study is based on a socio-environmental perspective, highlighting all the factors that affect ecosystems, such as: soil and air contamination; compromised water table, spread of diseases due to vector proliferation; and site assessment. Through a bibliographic survey, choice and evaluation, it was possible to identify that there was production of residues, many of them toxic, such as, for example, leftover wood from different origins, boards, paints, solvents and lime, and they were deposited in an appropriate manner. Therefore, the study proposes the need to adopt policies and waste management in civil construction and to carry out studies from a socio-environmental perspective.